2013
DOI: 10.1155/2013/576842
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of RNA and DNA Extraction from Fresh Pipelle and Archival Endometrial Tissues for Use in Gene Expression and SNP Arrays

Abstract: Identifying molecular markers of endometrial hyperplasia (neoplasia) progression is critical to cancer prevention. To assess RNA and DNA quantity and quality from routinely collected endometrial samples and evaluate the performance of RNA- and DNA-based arrays across endometrial tissue types, we collected fresh frozen (FF) Pipelle, FF curettage, and formalin-fixed paraffin-embedded (FFPE) hysterectomy specimens (benign indications) from eight women. Additionally, neoplastic and uninvolved tissues from 24 FFPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Traditionally, NGS techniques including RNAseq have employed fresh or fresh-frozen (FF) samples rather than formalin-fixed, paraffin-embedded (FFPE) samples due to the potential for degradation, with decreased exonic reads and increased intronic reads with FFPE samples (13). However, more recent studies of other human tissue, including brain, endometrial, lung, and breast cancers (14)(15)(16)(17)(18)(19)(20)(21)(22), demonstrated that FFPE samples stored for up to 32 years have been successfully analyzed with RNAseq, introducing the potential for future NGS analysis of widely available archival FFPE samples (23). FFPE samples are more readily available for children who have undergone a diagnostic biopsy, and eliminate the need for a separate research procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, NGS techniques including RNAseq have employed fresh or fresh-frozen (FF) samples rather than formalin-fixed, paraffin-embedded (FFPE) samples due to the potential for degradation, with decreased exonic reads and increased intronic reads with FFPE samples (13). However, more recent studies of other human tissue, including brain, endometrial, lung, and breast cancers (14)(15)(16)(17)(18)(19)(20)(21)(22), demonstrated that FFPE samples stored for up to 32 years have been successfully analyzed with RNAseq, introducing the potential for future NGS analysis of widely available archival FFPE samples (23). FFPE samples are more readily available for children who have undergone a diagnostic biopsy, and eliminate the need for a separate research procedure.…”
Section: Introductionmentioning
confidence: 99%
“…First, our study had a small sample size precluding definite conclusions which normally require a larger sample size to ensure a representative distribution of the population and to be considered representative of groups of people by statistical tests. Second, the use of FFPE tissue archives instead of fresh‐frozen (FF) tissues may be associated with known artifacts with impacts on the sequencing and the fidelity of expression profiles as previously proposed with limited quantity of DNA from FFPE samples 69‐71 . Lastly, the validation of targeted RNA‐seq by reverse transcriptase polymerase chain reaction (RT‐PCR) and HPV integration sites by fluorescent in situ hybridization (FISH) or PCR should be considered in the further study.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the use of FFPE tissue archives instead of fresh-frozen (FF) tissues may be associated with known artifacts with impacts on the sequencing and the fidelity of expression profiles as previously proposed with limited quantity of DNA from FFPE samples. [69][70][71] Lastly, the validation of targeted RNA-seq by reverse transcriptase polymerase chain reaction (RT-PCR) and HPV integration sites by fluorescent in situ hybridization (FISH) or PCR should be considered in the further study.…”
mentioning
confidence: 99%
“…Procurement of fresh tissue for banking or research protocols should be done as soon as possible as prolonged ischemia affects tissue quality for investigational purposes. Tissue procurement for research should not compromise pathologic evaluation 6–10. Therefore, a pathologist should be consulted in questionable cases.…”
Section: Should the Pathology Personnel Manage Requests For Fresh Tismentioning
confidence: 99%